Effect of Celebrity Endorsement in Advertising Activities by Product Type - Karasiewicz Grzegorz; Kowalczuk Martyna (International Journal of Management and Economics, 2014)
This article seeks to answer two related questions: are celebrity endorsements more likely to be result in a higher evaluation of the product being advertised than use of an anonymous individual (e.g. a typical consumer); and, if present, do these positive effects vary by product category? To answer these two questions research was conducted on a 237 student sample employing a quasi-experiment consisting of four groups (two product categories and two types of endorsers) using data collected through an online survey. The results indicate that celebrity endorsements do have a positive impact on the evaluation of durable goods, but do not affect the evaluation of frequently purchased products. This finding largely confirms the assumptions of the match-up model, the meaning transfer model, and the ELM model.